Response of forage mixtures to liming and different sources of phosphorus in two types of soils in Rio Grande do Sul, Brazil - Macedo, Walfreco; Jacques, Aino A. Vitor; Stammel, José Germano (Pesquisa Agropecuaria Brasileira, 2014)
The effects of different sources of phosphorus and the use of liming on the quality of two forage mixtures i.e. Rhodes grass + Desmodium infortum and Tall Fescue + Red clover were studied in the soils São Jerônimo (Latheritic Red Brown, distrophic) and Durox (Latosol Humic, eutrophic). Lime and phosphorus increased protein per hectare, but no influence was observed on the percentage of crude protein in the mixtures.